PERAN TRADISIONAL PETIK LAUT DALAM FUNGSIONALISME ISLAM DI JAWA TIMUR - Najiha, Rina; Habibullah, Achmad Luqman (Mozaic: Islamic Studies Journal, 2024)
This journal discusses the traditional role of Petik Laut in the context of Islamic functionalism, with a focus on local wisdom in East Java. Petik Laut is a traditional ceremony carried out by coastal communities as an expression of gratitude for the good fortune obtained from the sea. This research adopts a qualitative approach by collecting data through a literature study, which includes an analysis of related literature. The research results show that even though the Petik Laut tradition has experienced desacralization due to modernization, the East Java’s people still strive to maintain and preserve this tradition by making innovations in ceremonial processions. This reflects how the values of local wisdom and Islamic functionalism remain relevant in people's lives, as well as the importance of preserving culture as an identity and asset that must be passed on to future generations. It is hoped that this journal will provide insight into the interaction between tradition, modernization, and religious values in the context of coastal communities in Indonesia.